RITUAL HAI NIKI (BUANG PANAS) DITINJAU DARI ASPEK HUKUM PIDANA - Nitbani, Florensi T; Pello, Jimmy; Fanggi, Rosalind Angel; Wihelmus, Bhisa Vitus (Petitum Law Journal, 2025)
This research discusses the practice of Hai Niki, a post-circumcision ritual performed by the Atoni Pah Meto indigenous community on Timor Island. In this ritual, newly circumcised men are required to have sexual intercourse with women who are not their legal partners as part of the healing and purification process according to local beliefs. Although considered sacred in the local culture, this practice raises legal, ethical and human rights issues, especially because it places women as sexual objects without full control over their bodies. Using an empirical juridical approach, this research explores data through interviews with traditional leaders, perpetrators, and women involved. The results show that this ritual has the potential to violate national criminal law, including adultery, trafficking, and the protection of women and children. This research highlights the tension between customary law and formal state law. Therefore, a responsive and transformative legal approach is needed by emphasising the importance of legal awareness, gender equality education, and human rights protection, without ignoring local cultural identity.